Determination of dioxins in dyes and pigments with HRGC/HRMS - Križanec, B.; Brodnjak-Vončina, Darinka; Vončina, E.; Le Marechal, A. Majcen (Univerzita Pardubice, 2005)
Dioxins in some textile dyes and pigments may be a significant source of both human exposure and environmental contamination. Dyes and pigments contaminated with dioxins are the main sources of dioxins in textile industry. Further formations of dioxins can occur via dyeing and textile finishing processes at the conditions favoured for the generation of PCDD/Fs (high temperatures, alkaline conditions, UV radiation or other radical starters). Distribution of dioxins and their fate during textile processes were investigated. Textile disperse dye contaminated with dioxins was used in dyeing process and increasing of dioxins content during the process was observed.
Keywords: dioxiny; barvy; pigmenty; textilní průmysl; stanovení; chromatografické metody